BSCL2/Seipin deficiency in hearts causes cardiac energy deficit and dysfunction via inducing excessive lipid catabolism. Issue 4 (5th April 2022) - Zhou, Hongyi; Li, Jie; Su, Huabo; Li, Ji; Lydic, Todd A.; Young, Martin E; Chen, Weiqin
Abstract: Background: Heart failure (HF) is one of the leading causes of death worldwide and is associated with cardiac metabolic perturbations. Human Type 2 Berardinelli‐Seip Congenital Lipodystrophy (BSCL2) disease is caused by mutations in the BSCL2 gene. Global lipodystrophic Bscl2 −/− mice exhibit hypertrophic cardiomyopathy with reduced cardiac steatosis. Whether BSCL2 plays a direct role in regulating cardiac substrate metabolism and/or contractile function remains unknown. Methods: We generated mice with cardiomyocyte‐specific deletion of Bscl2 ( Bscl2 cKO ) and studied their cardiac substrate utilisation, bioenergetics, lipidomics and contractile function under baseline or after either a treatment regimen using fatty acid oxidation (FAO) inhibitor trimetazidine (TMZ) or a prevention regimen with high‐fat diet (HFD) feeding. Mice with partial ATGL deletion and cardiac‐specific deletion of Bscl2 were also generated followed by cardiac phenotyping. Results: Different from hypertrophic cardiomyopathy in Bscl2 −/− mice, mice with cardiac‐specific deletion of Bscl2 developed systolic dysfunction with dilation. Myocardial BSCL2 deletion led to elevated ATGL expression and FAO along with reduced cardiac lipid contents. Cardiac dysfunction in Bscl2 cKO mice was independent of mitochondrial dysfunction and oxidative stress, but associated with decreased metabolic reserve and ATP levels. Importantly, cardiac dysfunction in Bscl2 cKO mice could be partially reversed by FAO inhibitor TMZ, or prevented by genetic abolishment of one ATGL allele or HFD feeding. Lipidomic analysis further identified markedly reduced glycerolipids, glycerophospholipids, NEFA and acylcarnitines in Bscl2 cKO hearts, which were partially normalised by TMZ or HFD. Conclusions: We identified a new form of cardiac dysfunction with excessive lipid utilisation which ultimately causes cardiac substrate depletion and bioenergetics failure. Our findings also uncover a crucial role of BSCL2 in controlling cardiac lipid catabolism and contractile function and provide novel insights into metabolically treating energy‐starved HF using FAO inhibitor or HFD. Abstract : Cardiac deletion of BSCL2 causes ATGL overexpression, excessive fatty acid oxidation (FAO), drastic reduction of cardiac lipidome and ultimately energetic and contractile dysfunction in mice. Inhibiting FAO by partial ATGL deletion or trimetazidine and increasing lipid supply via high fat diet (HFD) feeding alleviate cardiac dysfunction caused by BSCL2 deficiency. BSCL2 is a novel protein indispensable for cardiac lipid metabolism and function.